Industry and empire : an economic history of Britain since 1750 - Hobsbawm, E. J. (London : Weidenfeld & Nicolson, 1968)
In Industry and Empire, Hobsbawm explores the origin and dramatic course of the industrial Revolution over two hundred and fifty years and its influence on social and political institutions. He describes and accounts for Britain's rise as the first industrial power, its decline from domination its special relation with the rest of the world, and the effects of this trajectory on the lives of its ordinary citizens." "This new edition includes a fascinating summary of events of the last twenty years, and an illuminating new conclusion.
Includes index.
Includes bibliographical references: p. 316-319.
aia 09/05/2018
Loans
Keywords: Industries; Great Britain